Optimization of the basic ethanolysis of ricin oil using the response surface methodology (2011)
Biodiesel production from ricin oil has been the focus of several pieces of research in recent years. However, few studies related to the basic ethanolysis of this non-edible vegetable oil have been reported. In this work, the optimum conditions for maximizing the conversion of the basic ethanolysis of ricin oil were determined using the response surface methodology (RSM). Experiments were conducted using a 2k rotable central composite design. The process variables were evaluated at two levels: alcohol/oil molar ratio (3/1- 10/1), catalyst quantity (1%-1.5%), and temperature (20 ºC-35 ºC). In order to ensure a good adjustment of the design, a quadratic model was implemented for the response variable. The model was able to predict 99.663% of the total variation of the system. The optimum conversion was of 93.64%, obtained with an alcohol/oil molar ratio of 9.86/1, a catalyst concentration of 1.2% with respect to oil weight, and a reaction temperature of 30 ºC, for a period of 1 hour.